Lemon Growing in the Florida Home Landscape - Jonathan H. Crane (EDIS)
HS1153, a 13-page fact sheet by Jonathan Crane, provides homeowners with an overview of this small vigorous citrus fruit tree — description, propagation, fruit production, placement in the landscape, care, pest management, concerns with lawn care, harvest, ripening, and storage, use and nutrition. Includes references. Published by the UF Department of Horticultural Sciences, December 2010.